Pengaruh Insentif dan Kepuasan Kerja terhadap Kinerja Pegawai pada Badan Pengelolaan Keuangan dan Aset Kabupaten Lampung Utara - Heylin Idelia Jayasinga; Yulistina Yulistina; Rini Windasari (Business and Enterpreneurship Journal (BEJ), 2020)
Organization is a system and human activities that work together to achieve some common goal through the division of labor and functions through responsibility. An organization requires human resources as a major supporter to achieve its intended purpose. Human Resources (HR) quality will contribute to promote a governmental organization as a container for improved performance. Research to be conducted kind of descriptive research, type of research is intending to make a presentation in a systematic, factual, and accurate about the facts - facts and properties - properties of a particular population. This type of research used in this research is a field (field reseach), which is a quantitative explanation is objective by explaining existing approaches. This study using 49 survey respondents. There are three variables in this study are: two (2) independent variable (X1 and X2) and 1 (one) in which the dependent variable incentives (X1) and job satisfaction (X2) as independent variables and employee performance (Y) as the dependent variable. From the data processing has successfully found an answer hypothesis that is as follows; Incentives are (X1) on employee performance (Y), with the level of influence (R-square) of 37.5%, which means that incentives have a relationship of 37.5% on employee performance. There is hubunugan between job satisfaction (X2) on employee performance (Y), with hubngan level of 38.2%, which means that job satisfaction empunyai relationship by 38.2% against the media results of job satisfaction. There is a relationship between incentive (X1), job satisfaction (X2) with employee performance (Y), with the level of relations of 39.7%, which means that there are incentives and belar media relations for 39.7% of the employee's performance.